Factor associated with prolong drain insertion time in breast cancer patients underwent surgery at Lamphun hospital - Tepjuk, Sasiwimol; Kiratipaisarl, Wuttipat (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Background: Breast cancer remains the most common malignancy in female patients, with surgical intervention being the primary treatment approach. One of the most common postoperative complications is the formation of seroma underneath the surgical incision. The standard management for seroma following modified radical mastectomy (MRM) or mastectomy typically involves the placement of subcutaneous closed-suction drainage. However, the optimal timing for drainage placement and the appropriate duration of drainage remains uncertain. We observed that some patients had their closed-suction drains removed earlier, leading to a shorter hospital stay compared to others. Therefore, this study aims to identify risk factors associated with prolonged indwelling of closed-suction drains after breast cancer surgery at Lamphun Hospital. Method: This retrospective cohort study entailed a total of 301 female patients, aged 20 years or older, who had a medical record of receiving breast cancer surgery in Lamphun Hospital from January 2019 to December 2023. Patients were divided into two groups: the "standard drainage" group, where drainage catheters were removed within 6 days, and the "prolonged drainage" group, where catheters remained in place for more than 6 days. Binary logistic regression analysis was performed to elicit risk factors associated with prolonged drainage. Results: Among 301 female breast cancer patients who underwent surgery at Lamphun Hospital, the mean age was 59.4 ± 10.4 years, and their average BMI was 24.1 ± 4.4 kg/m2. The most common comorbidities were hypertension, dyslipidemia, and diabetes mellitus, in the order of prevalence. Most patients had stage IIA breast cancer, and 98.6% of all patients underwent modified radical mastectomy (MRM). Of the 301 patients, 179 (59.5%) were in the prolonged drainage group. Statistically significant risk factors for prolonged drainage included: BMI (adjusted odds ratio [aOR] 2.42, 95% confidence interval [CI] = 1.20–4.90, p = 0.014), the number of axillary lymph nodes removed (aOR 1.30, 95% CI = 1.02–1.68, p = 0.033), and the 48-hour postoperative drain output (aOR 1.12, 95% CI = 1.07–1.18, p < 0.001). Conclusions: Prolonged drainage was significantly associated with higher BMI, a greater number of axillary lymph nodes removed, and greater 48-hour postoperative drain output. These findings may help guide postoperative care for patients at higher risk of requiring prolonged drainage. Keywords: Breast cancer, close suction drainage, duration of postoperative surgical drain, seroma